Geographical versus social displacement: the politics of return and post-war recovery in Northern Uganda. Issue 3 (3rd April 2019) - Khasalamwa-Mwandha, Sarah
ABSTRACT: The civil war in Northern Uganda in the period 1986–2006 fundamentally altered former ways of life and created diverse and complex needs. Protracted conflict and displacement create, reveal, and enforce vulnerability, which can undermine resilience. Based on in-depth interviews with internally displaced persons and returnees, both before and after their return to Amuru District and Gulu District, this article argues that war and displacement constitute more than a temporary disruption. The physical and social wounds of war are engraved and embedded in people's lives. Therefore, recovery interventions must take these effects into account to forge a new post-war future.